Research progress on the transmission and control of vancomycin-resistant Enterococcus in the environment: a review - Hui LI; Min JIN (Zhongguo gonggong weisheng, 2025)
Vancomycin-resistant enterococci (VRE) can cause various severe infectious diseases in humans, such as urinary tract infections, endocarditis, and neonatal sepsis. VRE is not only a significant risk factor for hospital-acquired infections but can also trigger severe environmental pollution and public health incidents. This article reviews the distribution and transmission routes of VRE in the environment. We summarize the environmental pollution control methods and clinical treatment of VRE infections. Not applicable. This review aims to provide a scientific basis for the prevention and control of VRE infections in the future.